The Heat Sensing Trpv1 Receptor Is Not a Viable Anticonvulsant Drug Target in the Scn1a+/− Mouse Model of Dravet Syndrome - Satpute Janve, Vaishali; Anderson, Lyndsey L.; Bahceci, Dilara; Hawkins, Nicole A.; Kearney, Jennifer A.; Arnold, Jonathon C. (Frontiers in Pharmacology, 2021)
Cannabidiol has been approved for the treatment of drug-resistant childhood epilepsies including Dravet syndrome (DS). Although the mechanism of anticonvulsant action of cannabidiol is unknown, emerging data suggests involvement of the transient receptor potential cation channel subfamily V member 1 (Trpv1). Pharmacological and genetic studies in conventional seizure models suggest Trpv1 is a novel anticonvulsant target. However, whether targeting Trpv1 is anticonvulsant in animal models of drug-resistant epilepsies is not known. Thus, we examined whether Trpv1 affects the epilepsy phenotype of the F1.Scn1a+/- mouse model of DS. We found that cortical Trpv1 mRNA expression was increased in seizure susceptible F1.Scn1a+/- mice with a hybrid genetic background compared to seizure resistant 129.Scn1a+/- mice isogenic on 129S6/SvEvTac background, suggesting Trpv1 could be a genetic modifier. Previous studies show functional loss of Trpv1 is anticonvulsant. However, Trpv1 selective antagonist SB-705498 did not affect hyperthermia-induced seizure threshold, frequency of spontaneous seizures or survival of F1.Scn1a+/- mice. Surprisingly, Trpv1 deletion had both pro- and anti-seizure effects. Trpv1 deletion did not affect hyperthermia-induced seizure temperature thresholds of F1.Scn1a+/-,Trpv1+/- at P14-16 but was proconvulsant at P18 as it reduced seizure temperature thresholds. Conversely, Trpv1 deletion did not alter the frequency of spontaneous seizures but reduced their severity. These results suggest that Trpv1 is a modest genetic modifier of spontaneous seizure severity in the F1.Scn1a+/- model of DS. However, the opposing pro- and anti-seizure effects of Trpv1 deletion and the lack of effects of Trpv1 inhibition suggest that Trpv1 is unlikely a viable anticonvulsant drug target in DS.